Penerapan Model Problem Based Learning (PBL) Berbantuan Media Audio Visual untuk Meningkatkan Hasil Belajar IPS Siswa Kelas 8 SMPN 3 Slahung - Munif Wajdi; Muhammad Hanif (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
This study aims to improve social studies learning outcomes for grade VIII SMPN 3 Slahung students by using a problem based learning model. The research method used is descriptive qualitative. This type of research is Classroom Action Research (CAR). The subjects of this research are 8th grade students of SMPN 3 Slahung. Data collection techniques in this research use observation sheets, test sheets and documentation. The data analysis technique used is qualitative analysis technique. The results of the research are as follows: 1) The implementation of learning using problem based learning in a row from cycle 1 and cycle II is 72.2 and 83.3; 2) While the average social studies learning outcomes in pre-cycle was 62.75, cycle 1 and cycle 2 were 71.59 and 80.35 respectively. This is already above the KKM, namely 72 and 3) Completeness of social studies learning outcomes in pre-cycle is 25% or 4 students, while in cycle 1 and cycle II it is 50% (8 students) and 93.75% (15 students). From the results of the research